2013
DOI: 10.5194/bg-10-5663-2013
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial Pacific peak in biological production regulated by nutrient and upwelling during the late Pliocene/early Pleistocene cooling

Abstract: The largest increase in export production in the eastern Pacific of the last 5.3 Myr (million years) occurred between 2.2 and 1.6 Myr, a time of major climatic and oceanographic reorganization in the region. Here, we investigate the causes of this event using reconstructions of export production, nutrient supply and oceanic conditions across the Pliocene–Pleistocene in the eastern equatorial Pacific (EEP) for the last 3.2 Myr. Our results indicate that the export production peak corresponds to a cold interval … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 51 publications
4
17
1
Order By: Relevance
“…In addition, this high productivity could not be explained through an iron fertilization process as could be expected in an iron-limited ocean region [Martin, 1990;Jickells et al, 2005], since iron values are relatively Paleoceanography 10.1002/2015PA002883 low before 1.85 Ma. A comparison with a sedimentary δ 15 N isotope record from the same marine core [Etourneau et al, 2013] also reveals low δ 15 N values specially during this interval prior to 1.85 Ma transition (Figure 5d). Etourneau et al [2013] interpreted this as a reflection of enhanced nitrate availability in the eastern equatorial Pacific system, suggesting that nutrient consumption was low relative to nutrient supply.…”
Section: Atmosphere-ocean Couplingmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, this high productivity could not be explained through an iron fertilization process as could be expected in an iron-limited ocean region [Martin, 1990;Jickells et al, 2005], since iron values are relatively Paleoceanography 10.1002/2015PA002883 low before 1.85 Ma. A comparison with a sedimentary δ 15 N isotope record from the same marine core [Etourneau et al, 2013] also reveals low δ 15 N values specially during this interval prior to 1.85 Ma transition (Figure 5d). Etourneau et al [2013] interpreted this as a reflection of enhanced nitrate availability in the eastern equatorial Pacific system, suggesting that nutrient consumption was low relative to nutrient supply.…”
Section: Atmosphere-ocean Couplingmentioning
confidence: 74%
“…A comparison with a sedimentary δ 15 N isotope record from the same marine core [Etourneau et al, 2013] also reveals low δ 15 N values specially during this interval prior to 1.85 Ma transition (Figure 5d). Etourneau et al [2013] interpreted this as a reflection of enhanced nitrate availability in the eastern equatorial Pacific system, suggesting that nutrient consumption was low relative to nutrient supply. Thus, the low δ 15 N values when export production was high indicate a significant supply of nutrients, including silicic acid and nitrate [Billups et al, 2013], to the eastern equatorial Pacific between 1.85 and 2.1 Ma.…”
Section: Atmosphere-ocean Couplingmentioning
confidence: 74%
“…Specifically, it has been suggested that intensification of the NHG and strengthening of the trade winds, over this time interval, resulted in lowering SST and shoaling of the thermocline in the EEP [Dekens et al, 2007;Ford et al, 2012;Lawrence et al, 2006;Steph et al, 2006Steph et al, , 2010. The fact that changes in productivity seem to be decoupled from these changes in SST and thermocline [Dekens et al, 2007;Etourneau et al, 2013;Lawrence et al, 2006] warrants further investigation and quantification of changes in export production.…”
Section: Introductionmentioning
confidence: 93%
“…Reorganizations in ocean circulation, export production, and climate history are reflected in the sedimentary record in the EEP [Kemp, 1995;Mayer et al, 1985Mayer et al, , 1992Van Andel, 1975]. Specifically, because of the relatively high proportional contribution of the EEP region to total ocean productivity and associated implications for climate, considerable effort has been devoted to the study of paleoproductivity, and fluctuation of productivity and export production in this region at multiple time scales have been reported [Calvo et al, 2011;Dekens et al, 2007;Diester-Haass et al, 2006;Etourneau et al, 2013;Gartner et al, 1987;King et al, 1998;Lawrence et al, 2006;Liu and Herbert, 2004;Mix et al, 2003;Robinson et al, 2009;Schneider and Schmittner, 2006;Steph et al, 2010]. To facilitate such reconstructions, a wide array of paleo-ocean productivity proxies have been utilized over the years.…”
Section: Introductionmentioning
confidence: 99%
“…The east-west tilt of the thermocline (shoaling to the east) allows the upwelling systems to tap into cooler, nutrient rich waters that originate in the Southern Ocean (Lehmann et al, 2018;Toggweiler et al, 1991) and are modified, in terms of nutrient content and nitrogen isotopes, in route to the equator (Rafter et al, , 2013. Published sedimentary nitrogen isotope records from EEP Ocean Drilling Program (ODP) Sites 849, 1239, and 1240 show lower values, on average, during the MPT relative to the last 1 Ma (Etourneau et al, 2013;. Published sedimentary nitrogen isotope records from EEP Ocean Drilling Program (ODP) Sites 849, 1239, and 1240 show lower values, on average, during the MPT relative to the last 1 Ma (Etourneau et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%